Finite element stress analysis of edentulous mandibles with different bone types supporting multiple-implant superstructures - De Almeida, Erika Oliveira [UNESP]; Rocha, Eduardo Passos [UNESP]; Freitas, Amílcar Chagas [UNESP]; Martin, Manoel (My University, 2010)
Purpose: The purpose of this study was to evaluate the influence of different types of bone on the stress distribution in the mandibular bone supporting a prefabricated bar-type implant prosthesis using three-dimensional finite element analysis. Materials and Methods: Four finite element models (M) of a completely edentulous mandibular arch were built. The bone types varied from type 1 to type 4 (M1, M2, M3, M4). The arch was restored using a prefabricated bar system supported by four interforaminal implants for the protocol prosthesis. Computer software was used to determine the stress fields. Three unilateral posterior loads (L) of 150 N were exerted on the prosthesis: L1, perpendicular to the prefabricated bar; L2, oblique (30 degrees) in the buccolingual direction; and L3, oblique (30 degrees) in the linguobuccal direction. The maximum principal stress (σmax) and the maximum principal strain (εmax) were obtained for cortical and trabecular bone. Results: Types 3 and 4 bone showed the highest σmax (MPa) in the cortical bone (19.9 and 18.2 for L1, 34.6 and 31.3 for L2, and 3.88 and 24.4 for L3, respectively). The maximum principal strain (εmax) was observed in type 4 cortical bone for all loads (1.80 for L1, 2.4 for L2, and 2.36 for L3). Conclusions: The cortical bone in M3 and M4 showed the highest stress concentration in the axial and buccolingual loading conditions. Bone types 1 and 2 showed the lowest stress concentrations. For the linguobuccal loading condition, the cortical bone in M4 showed the highest stress concentration, followed by bone types 3, 2, and 1. Cortical bone in M4 showed the highest strain for all loading conditions. The bone type might not be the only decisive factor to influence the stress distribution the bone supporting an implant prosthesis anchored by a prefabricated bar. © 2010 by Quintessence Publishing Co Inc.
Keywords: Biomechanics; Bone; Dental implants; Finite element analysis; Osseointegration